2017
DOI: 10.4172/2167-7182.1000452
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Frailty in the Community-Dwelling Elderly Population. A Two-Year Follow-Up Cohort Study

Abstract: Background: Frailty is a highly prevalent geriatric syndrome and a major public health problem. Designing effective preventive measures requires an understanding of frailty mechanisms and risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…This study has successfully reported the incidence rate of CF at a rate of 7.1 per 100 person-years among older adults who did not exhibit CF at the baseline. The incidence rate of mild cognitive impairment (MCI) and physical frailty was 10.5 and 6.8 per 100 person-years, as reported in previous local studies [38,39]. Accordingly, the incidence rate of CF from the recent study was relevant and proportional to the reported incidence rate for both geriatric syndromes.…”
Section: Discussionsupporting
confidence: 59%
“…This study has successfully reported the incidence rate of CF at a rate of 7.1 per 100 person-years among older adults who did not exhibit CF at the baseline. The incidence rate of mild cognitive impairment (MCI) and physical frailty was 10.5 and 6.8 per 100 person-years, as reported in previous local studies [38,39]. Accordingly, the incidence rate of CF from the recent study was relevant and proportional to the reported incidence rate for both geriatric syndromes.…”
Section: Discussionsupporting
confidence: 59%
“…To estimate the global incidence of frailty, data were included from 46 studies. 41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,83,84,85,86 Among people without frailty at baseline who survived a median follow-up of 3.0 (range, 1.0-11.7) years, 13.6% (13 678 of 100 313) became frail. The pooled incidence rate of frailty was 43.4 (95% CI, 37.3-50.4; I 2 = 98.5%) cases per 1000 person-years (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies 41,42,46,51,53,57,59,60,65,66,67,68,69,71,72,77,79,80,81,82,83 reported data on the global incidence of prefrailty among 32 268 community-dwelling older adults who were robust at baseline and survived a median follow-up of 2.5 (range, 1.0-10.0) years. During the follow-up, 30.9% (9974 of 32 268) became prefrail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In a 2-year cohort study also showed that low physical activity and depression as risk factors for frailty. 16 Other variables such as age, educational level, BMI, and disability do not show significant relationship with frailty. This study recruited a sample from an urban area with middle socioeconomic status, which differentiates this study from another study in Malaysia that recruited a sample in a rural area with a low socioeconomic status.…”
Section: Discussionmentioning
confidence: 92%